Radical frame semantics and biblical Hebrew : exploring lexical semantics - Shead, Stephen L. (Biblical interpretation series, 2011)
ince James Barrs work in the 1960s, the challenge for Hebrew scholars has been to continue to apply the insights of linguistic semantics to the study of biblical Hebrew. This book begins by describing a range of approaches to semantic and grammatical analysis, including structural semantics, cognitive linguistics and cognitive metaphors, frame semantics, and William Crofts Radical Construction Grammar. It then seeks to integrate these, formulating a dynamic approach to lexical semantic analysis based on conceptual frames, using corpus annotation. The model is applied to biblical Hebrew in a detailed study of a family of words related to exploring, searching, and seeking. The results demonstrate the value and potential of cognitive, frame-based approaches to biblical Hebrew lexicology.